2013
DOI: 10.1111/nph.12104
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of plants to changing atmospheric CO2 concentration: from the geological past to the next century

Abstract: 1077I.1078II.1079III.1080IV.1081V.1084VI.1087VII.10881089References1089 Summary The rate of CO2 assimilation by plants is directly influenced by the concentration of CO2 in the atmosphere, ca. As an environmental variable, ca also has a unique global and historic significance. Although relatively stable and uniform in the short term, global ca has varied substantially on the timescale of thousands to millions of years, and currently is increasing at seemingly an unprecedented rate. This may exert profound im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
320
2
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 363 publications
(339 citation statements)
references
References 236 publications
(342 reference statements)
14
320
2
3
Order By: Relevance
“…The breakpoint was identified as 1982, which corresponds to the approximate time when SO 2 emissions began to decline in the United States. This result was surprising because it is counter to the widely observed stomatal response of plants to increasing CO 2 in the 20th century (11,23). Here, decreasing Δ 13 C before ∼1980 suggest stomatal closure as if the trees were responding to increasing atmospheric CO 2 , yet the reversal and increases in Δ 13 C after 1980 suggest reduced stomatal regulation to CO 2 (Fig.…”
Section: Significancecontrasting
confidence: 48%
See 1 more Smart Citation
“…The breakpoint was identified as 1982, which corresponds to the approximate time when SO 2 emissions began to decline in the United States. This result was surprising because it is counter to the widely observed stomatal response of plants to increasing CO 2 in the 20th century (11,23). Here, decreasing Δ 13 C before ∼1980 suggest stomatal closure as if the trees were responding to increasing atmospheric CO 2 , yet the reversal and increases in Δ 13 C after 1980 suggest reduced stomatal regulation to CO 2 (Fig.…”
Section: Significancecontrasting
confidence: 48%
“…2C) due to a 23% increase in A and an 18.5% decrease in g c . Many dendroisotopic studies have concluded that the small but progressive increases in atmospheric CO 2 over the last century have improved iWUE (23,33), and suggest that a fundamental way that increasing atmospheric CO 2 stimulates tree growth and forest productivity is by improving the efficiency that trees are using water. Here, acid deposition over many decades contributed to a large portion of the increase in iWUE of Juniperus, and these data signify that the effects of increasing CO 2 on iWUE can be greatly overestimated if other environmental influences are not considered in these estimates.…”
Section: Significancementioning
confidence: 99%
“…Whereas the gas exchange of CO 2 and water vapor at the stomatal pore is a physical process controlled by both the ratio in partial pressure gradients and gas diffusivities (4,5), terrestrial plants are able to capture carbon more efficiently under water deficit. Both short-term leaf gas exchange measurements and 13 C isotope discrimination analyses revealed increases of the instantaneous water use efficiency (insWUE) and intrinsic WUE (iWUE), respectively, by a factor of 1.5-2.5 in wheat and other species (6,7).…”
mentioning
confidence: 99%
“…This adaptation is usually in the direction that would tend to counteract the physiological effects of the change in c a (e.g. higher D with lower c a increases stomatal conductance to counteract the initial drop in CO 2 assimilation rate; Franks et al, 2012bFranks et al, , 2013. What remains unclear about this simple principle is how to characterize this sensitivity quantitatively for the purpose of simulation or prediction.…”
Section: Stomatal Size Density and Conductance Through Deep Timementioning
confidence: 99%
“…1; see discussion in Franks et al, 2013). Importantly, stomata behave as both negative and positive feedback elements, depending on the process.…”
mentioning
confidence: 99%